The study of the cold and heat properties of Dianthus superbus and Odontites vulgaris based on multi-sample metabolomics and gut microbiota analysis: Exploring material and energy metabolism mechanisms - Yafeng Zhuang; Xiangxi Meng; Jiayin Chang; Xiaolei Jiang; Hong Chang; Minhui Li (Pharmacological Research - Modern Chinese Medicine, 2025)
Objective: Dianthus superbus (DS)and Odontites vulgaris (OV) are crucial components of the Mongolian medicine ''Bashaga'', each possessing unique efficacy. However, their cold and heat natures remain to be experimentally verified. The aim of this study is to validate the medicinal natures of DS and OV and to elucidate the underlying mechanisms from the perspectives of substance and energy metabolism as well as gut microbiota. Methods: In this study, Anemarrhena asphodeloides (AA, a cold-natured traditional Chinese medicine) and Cinnamomum cassia (CC,a heat-natured traditional Chinese medicine) were used as references to explore the impacts of DS and OV on the material and energy metabolism, multi-sample metabolomics, and gut microbiota in normal rats. This method aims to evaluate the medicinal properties of these plants and clarify their underlying mechanisms. Results: In terms of material and energy metabolism, the content of Sodium-Potassium Adenosine Triphosphatase (Na⁺/ K⁺ -ATP) in DS and OV was lower than the normal level (p < 0.05). In DS, Pyruvate Kinase (PK) was significantly decreased (p < 0.01), Adenylate Kinase (ADK) was decreased (p < 0.001), and Citrate Synthase (CS) was increased (p < 0.05). In OV, ADK was decreased (p < 0.01) and Glycogen Synthase Kinase 3 Alpha (GSK - 3α) was increased (p < 0.05). AA showed a similar situation. In terms of metabolomics, the metabolic profiles and clustering heatmaps of DS, OV, and AA were similar. AA affected the tryptophan-related metabolic pathways, while CC affected the glutamate-related metabolic pathways. Regarding the gut microbiota, DS, OV, and AA all increased the diversity and richness of the microbiota. At the phylum and genus levels, the composition of the microbiota was similar, and the abundances of various microbiota changed differently. Conclusion: DS and OV exhibit cold-natured characteristics, as evidenced by their impacts on metabolism and gut microbiota. These findings provide preliminary insights into the potential mechanisms underlying their medicinal properties.